The American H.D. - Debo, Annette, 1964- (University of Iowa Press, 2012)
"In The American H.D., Annette Debo considers the significance of nation in the artistic vision and life of the modernist writer Hilda Doolittle. Her versatile career stretching from 1906 to 1961, H.D. was a major American writer who spent her adult life abroad; a poet and translator who also wrote experimental novels, short stories, essays, reviews, and a children's book; a white writer with ties to the Harlem Renaissance; an intellectual who collaborated on avant-garde films and film criticism; and an upper-middle-class woman who refused to follow gender conventions. Her wide-ranging career thus embodies an expansive narrative about the relationship of modernism to the United States and the nuances of the American nation from the Gilded Age to the Cold War. Making extensive use of material in the Beinecke Rare Book and Manuscript Library at Yale - including correspondences, unpublished autobiographical writings, family papers, photographs, and Professor Norman Holmes Pearson's notes for a planned biography of H.D. - Debo's American H.D. reveals details about its subject never before published. Adroitly weaving together literary criticism, biography, and cultural history, The American H.D. tells a new story about the significance of this important writer. Written with clarity and sincere affection for its subject, The American H.D. brings together a sophisticated understanding of modernism, the poetry and prose of H.D., the personalities of her era, and the historical and cultural context in which they developed: America's emergence as a dominant economic and political power that was riven by racial and social inequities at home."--Project Muse